2012
DOI: 10.1007/s00330-012-2585-0
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and speed of robotic assisted needle interventions using a modern cone beam computed tomography intervention suite: a phantom study

Abstract: When using the proposed robot device in a CBCT intervention suite, highly accurate needle-based interventional punctures are possible in a reasonable timely manner in single as well as in double oblique trajectories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 20 publications
1
32
1
Order By: Relevance
“…However, the applicator was readjusted a few times to increase accuracy, which reduced the applicator deviation to 6.2 mm and 1.9 mm respectively. Previous studies on stable materials (phantoms and vertebra) using robotic devices during fluoroscopic punctures arrived at average needle tip deviations of 1.1 mm and 4.6 mm after additional fine needle adjustments [19,20]. It is of importance to note that the two mentioned studies were performed on stable structures in contrast to the present study, where the patient's liver may have moved involuntarily.…”
Section: Discussionmentioning
confidence: 68%
“…However, the applicator was readjusted a few times to increase accuracy, which reduced the applicator deviation to 6.2 mm and 1.9 mm respectively. Previous studies on stable materials (phantoms and vertebra) using robotic devices during fluoroscopic punctures arrived at average needle tip deviations of 1.1 mm and 4.6 mm after additional fine needle adjustments [19,20]. It is of importance to note that the two mentioned studies were performed on stable structures in contrast to the present study, where the patient's liver may have moved involuntarily.…”
Section: Discussionmentioning
confidence: 68%
“…A previously published phantom study demonstrated that the new compact robotic device, iSYS1 (Medizintechnik GmbH, Kitzbuehel, Austria) allows highly accurate needle guidance in a reasonable timely manner in single as well as double oblique trajectories 11. The purpose of the current cadaver study was to evaluate the performance of the proposed robotic device for needle interventions during spinal interventions in terms of accuracy and required time in a dedicated C-arm based CBCT suite.…”
Section: Introductionmentioning
confidence: 99%
“…in their work that CBCT-guided interventions conducted with the help of a robotic arm as needle holder can be conducted with high accuracy and in a timely manner in a phantom 14,15 . In our experience most image-guided interventions are still conducted using a free-handed approach, however, navigational tools are becoming more important as interventions become more complex 1,2,7,8,10,11 .…”
Section: Schulz Et Al and Tovar-arriaga Et Al Both Demonstratedmentioning
confidence: 99%